(untitled) (International Conference on Computers in Education, 2013)
This study aimed to find out if students’ satisfaction in English classes is associated with the frequency of teachers using technology teaching support, such as E-learning or web-based learning resources. The participants for this study were students who enrolled in the author’s classes and therefore were considered as convenient samples (n＝151). They were given extra credits to complete the questionnaire that was designed for the purpose of this study. This study found that student satisfaction for English classes is significantly positively associated with the frequency of teachers using technology teaching support ( r＝.742, p＜. 01). Furthermore, after conducting Chi-square test, Pearson value showed that there were four items (Q 1, 2, 7, 17) student ’s satisfaction was significant different among three different programs (four-year program, two-year program, and five-year program.) In addition, six items (Q 1, 3, 5, 7, 8, 17) student ’s satisfaction appeared significantly different among freshmen, sophomores, juniors, and seniors. Lastly, limitation, implications and suggestions for further research are addressed.